Breadth and Specificity in Pleiotropic Protein Kinase A Activity and Environmental Responses - Kocik, Rachel A.; Gasch, Audrey P. (Frontiers in Cell and Developmental Biology, 2022)
Protein Kinase A (PKA) is an essential eukaryotic regulator that plays fundamental roles in a wide range of organismal processes, including growth control, learning and memory, cardiovascular health, and development. PKA mediates these responses through the direct regulation of metabolic enzymes, transcription and translation factors, organelles, and structural proteins, often in response to environmental cues, albeit with different upstream inputs and unique regulatory outputs depending on the conditions. A major question is how PKA maintains signaling specificity and precision in the face of its broad participation in numerous functions, especially during environmental responses in which only a subset of PKA-controlled processes must respond. Research over the years has uncovered multiple strategies that cells use to modulate PKA activity and specificity, from tissue-specific expression to subcellular anchoring. This review highlights recent advances in our understanding of PKA signaling control including subcellular targeting, phase separation, feedback control, and standing waves of allosteric regulation. PKA serves as a model for how the same regulatory factors can serve broad pleiotropic functions but maintain specificity in localized control.